2019
DOI: 10.1021/acsami.9b12482
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Effect of Polymer Regioregularity on the Thermal Stability of Polymer Solar Cells

Abstract: Thermal stability is a bottleneck toward commercialization of polymer solar cells (PSCs). The effect of PCBM aggregation on a multilength scale on the bulk-heterojunction (BHJ) structure, performance, and thermal stability of PSCs is studied here by grazing-incidence small- and wide-angle X-ray scattering. The evolution of hierarchical BHJ structures of a blend film tuned by regioregularity of polymers from the as-cast state to the thermally unstable state is systematically investigated. The thermal stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…The factors that contribute to the reduction in operational efficiency of OPV cells and modules over time are several and have been clearly identified. [320][321][322][323][324][325][326][327][328][329] Degradation factors that are common to all OPV devices include: photochemical and photo physical degradation of the active layer materials and interfaces; [330][331][332] morphological degradation [333,334] due to high thermal stress under operation; as well as, a series of degradation events that can be initiated by the ingress of H 2 O and O 2 in poorly sealed devices. [335][336][337] Additionally, there are some degradation factors specific to OPV modules, including electrical stress [338] and degradation at the cell interconnections.…”
Section: Encapsulation and Stability Testing Of Large Area Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors that contribute to the reduction in operational efficiency of OPV cells and modules over time are several and have been clearly identified. [320][321][322][323][324][325][326][327][328][329] Degradation factors that are common to all OPV devices include: photochemical and photo physical degradation of the active layer materials and interfaces; [330][331][332] morphological degradation [333,334] due to high thermal stress under operation; as well as, a series of degradation events that can be initiated by the ingress of H 2 O and O 2 in poorly sealed devices. [335][336][337] Additionally, there are some degradation factors specific to OPV modules, including electrical stress [338] and degradation at the cell interconnections.…”
Section: Encapsulation and Stability Testing Of Large Area Devicesmentioning
confidence: 99%
“…For example, chemical modification of polymer donors, either modification of backbone or side chains, has proved effective to improve the stability of OPV devices. [212,339,340] An increase in the polymer molecular weight [341][342][343] and in polymer regioregularity [333] have also been shown to produce more stable devices. NFA-based OPVs, have been demonstrated to exhibit, in general, considerably higher thermal and photochemical stability than the corresponding fullerene based OPVs.…”
Section: Encapsulation and Stability Testing Of Large Area Devicesmentioning
confidence: 99%
“…56,57 Huang et al investigated the effect of RR of P3HT in the blend phenyl-C 61butyric acid methyl ester (PCBM)−P3HT: by increasing the RR of the polymer, the thermal stability improved. 58 Kim et al also showed that by enhancing the RR the photovoltaic efficiency of the device enhanced, and the influence of the RR on the improvement of the solar cell performance could be related to the enhanced optical absorption and transport resulting from the organization of the P3HT chain and domain, 59 while Sivula and co-workers showed that on increasing the RR, the stability decreased. 60 Chuang et al reported that the RR effect on optical anisotropy increased the power-conversion efficiency of large-area P3HT/PCBM-based organic solar cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This is justified by the growth structure of the lamellae of the PEG polymer, which thickens as the MW increases up to 4 kDa, thus increasing the melting point of the material. For MWs higher than 4 kDa, the lamellae thickness does not change much because of a folded chain crystal growth, so no further change is observed in the thermal stability. , Huang et al investigated the effect of RR of P3HT in the blend phenyl-C 61 -butyric acid methyl ester (PCBM)–P3HT: by increasing the RR of the polymer, the thermal stability improved . Kim et al also showed that by enhancing the RR the photovoltaic efficiency of the device enhanced, and the influence of the RR on the improvement of the solar cell performance could be related to the enhanced optical absorption and transport resulting from the organization of the P3HT chain and domain, while Sivula and co-workers showed that on increasing the RR, the stability decreased .…”
Section: Introductionmentioning
confidence: 99%
“…As a new-generation renewable energy device, organic solar cells have attracted more attention because of their advantages such as light weight and flexibility. The highest power conversion efficiency (PCE) value exceeded 18%; however, how to solve the long-term stability influenced by oxygen, water, irradiation, heating, diffusion of electrodes and buffer layer materials, and mechanical stress becomes a key problem to realize commercialization. Especially, the solar cells often operate under continuous illumination, and the working temperature could reach as high as 90 °C . Thus, the thermal stability becomes a vital barrier to overcome for the commercial use of organic solar cells.…”
Section: Introductionmentioning
confidence: 99%